EVALUASI TATA LETAK FASILITAS DI PT MBG PUTRA MANDIRI YOGYAKARTA - Elsya Tarigan; Sri zetli (Universitas Putera Batam, 2022)
Planning a company's facilities is very important to pay attention to, because if the layout of the company is good and right, it will indirectly save in terms of production costs. PT MBG Putra Mandiri is a company engaged in manufacturing which has eight departments for the production process, where in its layout there are shortcomings due to the back and forth movement which indirectly causes a very large total material handling cost and energy expended, also getting bigger. In solving the problem, the algorithm used is the CRAFT and BLOCPLAN algorithms because based on research conducted by G. Anisa K. (2002), the best algorithms to solve the problem of facility layout that have less than ten departments are the CRAFT and BLOCPLAN algorithms. Based on the results obtained from each algorithm, the algorithm that provides the lowest total material handling costs is the BLOCPLAN and CRAFT algorithms, which are Rp 427.520,00 which when compared to the initial layout of Rp 3.068.124,00 and has a difference of Rp 2.640.604,00.